JUDICIAL REVIEW OF CRIMINAL OFFENSES ON CUSTOMER DATA THEFT OF BANKS IMPLICATED IN THE LOSS OF CUSTOMER’S MONEY - Cahyono, Febrian Dwi Putra; Hartantien, Sinarianda Kurnia (jfpublisher, 2023)
Technological developments in the banking sector intend to improve the quality service for the community, especially those who are often called customers in banking transactions. The convenience provided in the banking sector has contributed to several crimes regarding the criminal act of customer data theft, considering that technological advances in banking services have facilitated the perpetrators to commit their crimes. The purpose of this research is to examine and obtain a legal perspective on the criminal act of customer data theft. The method of this research is normative juridical. According to the findings in this research, it is obtained that the positive legal regulation of the criminal offense regarding customer data theft is intended to provide relevant sanctions and legal protection to the perpetrators and victims of crime. The existence of criminal liability for the perpetrators of criminal acts of customer data theft, requires the application of criminal sanctions as a real effort to eradicate these crimes so as not to cause many losses.